In Silico study of anticancer activity of some marine alkaloids from marine sources on human osteosarcoma - Tamimount, Khouloud; Khelifa, Anis; Grinat, Mouna; Benarous, Khadidja (Laghouat : Université Amar Telidji - Département de biologie, 2023)
Osteosarcoma, a prevalent form of bone cancer predominantly affecting children and adolescents, has been the subject of extensive research efforts. Recent advances in molecular genetic research have revolutionized our understanding of the disease's origins, leading to the discovery of targeted therapeutic approaches. In this study, our objective is to conduct an insilico investigation on the anti-tumoral properties of seven marine alkaloids against the human osteosarcoma cell line SaOS2, targeting newly identified oncogenic proteins, including four enzymes and one receptor that have participated in major pathways of the tumor cells. The seven marine alkaloids examined in this study are as follows: Coscinamide A (Mol1),Leucettamine B (Mol2),Polyandrocarpamine A (Mol3), Coscinamide B (Mol4), Coscinamide C (Mol5), Dispacamide (Mol6), and Eudistomin Y1 (Mol7). To achieve this goal, we employed several computational methods. Firstly, we performed molecular docking (MD) using Autodock Vina to evaluate the binding affinity of the ligand-protein complexes. Additionally, we obtained the pharmacokinetic properties and toxicity profiles of these alkaloids using ADMET's online servers. We conducted a biological cytotoxicity prediction using the CLCPred online server, which confirmed that the antitumoral effect is not limited to osteosarcoma alone but is also applicable to various other types of cancer. We also utilized the STRING database to predict protein-protein interactions and investigate potential pathways and activities. The results of our study indicate that mol5 exhibited the highest affinity for the ER target, while mol7 demonstrated the highest affinity for the PIM-1 and HSP90 targets. For the T311M HDAC8 and BMP-2 targets, Mol4 and Mol1 respectively are the highest score. Detailed information of the best interactions is presented in the results section. Importantly, despite the general toxicity of alkaloids, our investigation revealed that the seven compounds demonstrated a favorable safety profile and exhibited non-toxic characteristics, suggesting their viability for use. These promising results need further validation through in vitro and in vivo studies to confirm the effectiveness of these marine alkaloids in treating osteosarcoma.